The LN54 Radiation Hybrid Map of Zebrafish Expressed Sequences - Hukriede, Neil; Fisher, Dan; Epstein, Jonathan; Joly, Lucille; Tellis, Patricia; Zhou, Yi; Barbazuk, Brad; Cox, Kristine; Fenton-Noriega, Laura; Hersey, Candace; Miles, Jennifer; Sheng, Xiaoming; et al. (Genome Research, 2001)
To increase the density of a gene map of the zebrafish, Danio rerio, we have placed 3119 expressed sequence tags (ESTs) and cDNA sequences on the LN54 radiation hybrid (RH) panel. The ESTs and genes mapped here join 748 SSLp markers and 459 previously mapped genes and ESTs, bringing the total number of markers on the LN54 RH panel to 4226. Addition of these new markers brings the total LN54 map size to 14,372 cR, with 118 kb/cR. The distribution of ESTs according to linkage groups shows relatively little variation (minimum, 73; maximum, 201). This observation, combined with a relatively uniform size for zebrafish chromosomes, as previously indicated by karyotyping, indicates that there are no especially gene-rich or gene-poor chromosomes in this species. We developed an algorithm to provide a semiautomatic method for the selection of additional framework markers for the LN54 map. This algorithm increased the total number of framework markers to 1150 and permitted the mapping of a high percentage of sequences that could not be placed on a previous version of the LN54 map. The increased concentration of expressed sequences on the LN54 map of the zebrafish genome will facilitate the molecular characterization of mutations in this species.
10.1101/gr.210601